Missing Millie Benson : the secret case of the Nancy Drew ghostwriter and journalist - Rubini, Julie (Biographies for young readers., 2015)
"Missing Millie Benson is as lively and compelling as a Nancy Drew Mystery Story. For anyone who loves Nancy, getting to know the woman who first brought her to life in this wonderful biography is not just a treat but a necessity an inspiration to young writers and sleuths alike!" Growing up in Ladora, Iowa, Mildred "Millie" Benson had ample time to develop her imagination, sense of adventure, and independence. Millie left her small hometown to attend the University of Iowa, where she became the first person to earn a master's degree from the school of journalism. While still a graduate student, Millie began writing for the Stratemeyer Syndicate, which published the phenomenally popular Hardy Boys series, among many others. Soon, Edward Stratemeyer tapped Millie for a new series starring amateur sleuth Nancy Drew, a young, independent woman not unlike Millie herself. The syndicate paid its writers a flat fee for their work and published the books under pseudonyms. Under the pen name Carolyn Keene, Millie went on to write twenty-three of the first thirty books of the Nancy Drew Mystery Stories. In all, Millie wrote more than a hundred novels for young people under her own name and under pseudonyms. Millie was also a journalist for the Toledo (Ohio) Times and The Blade. At the age of sixty-two she obtained her pilot's license and combined her love of aviation with her passion for writing, sharing her travels and adventures with readers. Follow the clues throughout Missing Millie to solve the mysteries of this ghostwriter, journalist, and adventurer. "--